A reduced-toxicity myeloablative conditioning approach for hematopoietic cell transplant in juvenile myelomonocytic leukemia - Elsabagh, Eman; Gallant, Rachel; Goldberg, Lior; Sharma, Aditya; Martin, Paul L.; Driscoll, Timothy A.; Bauchat, Andrea; Kurtzberg, Joanne; Spencer, LaTarsha; Aguayo-Hiraldo, Paibel I.; Kapoor, Neena; Mahadeo, Kris M.; et al. (Frontiers in Oncology, 2025)
IntroductionAllogeneic hematopoietic cell transplantation (HCT) is a potentially curative treatment for most children with juvenile myelomonocytic leukemia (JMML), but overall survival remains poor at 50%. Given its rarity and heterogeneity, there is no standard HCT conditioning regimen for JMML.MethodsRetrospective study of consecutive patients with JMML who underwent HCT using a busulfan/ melphalan backbone conditioning regimen (n=17) at two academic centers.ResultsThe median age at HCT was 1.9 (range 0.7-6.0) years. At a median follow up of 7.6 (range 2.9-21.5) years, 100% disease-free (DFS) and overall survival (OS), with prompt immune reconstitution were observed. This cyclophosphamide-sparing approach was associated with no transplant related mortality.DiscussionGiven excellent clinical outcomes at extended follow-up, prospective studies are needed to confirm our findings in this ultra-rare disease.